2018
DOI: 10.1177/0969733017747957
|View full text |Cite
|
Sign up to set email alerts
|

How to succeed with ethics reflection groups in community healthcare? Professionals’ perceptions

Abstract: Both internal and external factors seem to influence the organization of ethics reflection group. The municipalities' instabilities challenging this work, and perceived as a clear inhibitor for the development. The participants experienced that the facilitator is the most important success factor for establishing, carrying out, and to succeed with ethics reflection groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“… 19 Facilitator-led ethical reflection in groups was the most applied intervention among the participating municipalities. 20 Staff indicated that group reflection on ethics contributed significantly to perceived quality and competence and was considered a meaningful activity promoting better handling of ethical dilemmas. 21 However, organizational instabilities in community healthcare may hinder achievements, 20 and evaluations in 2014 22 showed that only a minority of the municipalities had implemented systematic ethical reflection.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 Facilitator-led ethical reflection in groups was the most applied intervention among the participating municipalities. 20 Staff indicated that group reflection on ethics contributed significantly to perceived quality and competence and was considered a meaningful activity promoting better handling of ethical dilemmas. 21 However, organizational instabilities in community healthcare may hinder achievements, 20 and evaluations in 2014 22 showed that only a minority of the municipalities had implemented systematic ethical reflection.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Staff indicated that group reflection on ethics contributed significantly to perceived quality and competence and was considered a meaningful activity promoting better handling of ethical dilemmas. 21 However, organizational instabilities in community healthcare may hinder achievements, 20 and evaluations in 2014 22 showed that only a minority of the municipalities had implemented systematic ethical reflection. Among promoting factors, health personnel find that organizational support – especially from department management – is an important driving force, in that someone organizes and actively expects results from the ethics reflection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collective systematic ethics work may foster greater awareness of ethical aspects, personal and professional development, understanding and respect for colleagues and patients, along with cooperation and new ways to approach di cult situations (13,(32)(33)(34). This can be done by ethics re ection groups, as in the Norwegian project in municipal healthcare services which resulted in improvements in these areas; handling ethical challenges, employee cooperation, service quality and relations to patients and relatives (35,36).…”
Section: Ethical Challenges In Clinical Practicementioning
confidence: 99%